Women and Racial Minorities in the Boardroom: How Do Directors Differ? - Hillman, Amy J.; Cannella, Albert A.; Harris, Ira C. (Journal of Management, 2002)
In this paper, we examine how the attributes of female and racial minority directors differ from those of white males. We track a sample of white male, white female, African-American female and African-American male directors who serve on Fortune 1000 boards and find differences in occupational background, education, and patterns of board affiliation. Female and African-American directors are more likely to come from non-business backgrounds, are more likely to hold advanced degrees, and join multiple boards at a faster rate than white male directors.